Quantitative Easing and Credit Rating Agencies - Abidi, Nordine; Falagiarda, Matteo; Miquel-Flores, Ixart.. (Washington, D.C. : International Monetary Fund, 2022)
This paper investigates the behaviour of credit rating agencies using a natural experiment in monetary policy. We exploit the corporate QE of the Eurosystem and its rating-based specific design which generates exogenous variation in the probability for a bond of becoming eligible for outright purchases. We show that after the launch of the policy, rating activity was concentrated precisely on the territory where the incentives of market participants are expected to be more sensitive to the policy design. Our findings contribute to better assessing the consequences of the explicit reliance on CRAs ratings by central banks when designing monetary policy. They also support the Covid-19 monetary stimulus, and in particular the waiver of private credit rating eligibility requirements applied to recently downgraded issuers.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Central Banks and Their Policies; Financial Markets and the Macroeconomy; Investment Banking; Monetary Policy; Venture Capital